2006
DOI: 10.1038/sj.emboj.7601450
|View full text |Cite
|
Sign up to set email alerts
|

hRpn13/ADRM1/GP110 is a novel proteasome subunit that binds the deubiquitinating enzyme, UCH37

Abstract: The 26S proteasome catalyzes the degradation of most proteins in mammalian cells. To better define its composition and associated regulatory proteins, we developed affinity methods to rapidly purify 26S proteasomes from mammalian cells. By this approach, we discovered a novel 46-kDa (407 residues) subunit of its 19S regulatory complex (previously termed ADRM1 or GP110). As its N-terminal half can be incorporated into the 26S proteasome and is homologous to Rpn13, a 156-residue subunit of the 19S complex in bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
228
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(238 citation statements)
references
References 34 publications
10
228
0
Order By: Relevance
“…Deletion of ADRM1 by siRNA does not lead to global accumulation of ubiquitinated cellular proteins or changes in proteasome expression, suggesting that ADRM1 must have a specialized role in proteasome function (8). Shorty after the above report, three independent groups confirmed that ADRM1 is a novel 19S proteasome cap-associated protein, but they further revealed a unique role for ADRM1 in protein degradation (7,9,10). These groups found that ADRM1 interacts with the carboxyl-terminal tail of ubiquitin C-terminal hydrolase UCH37 and recruits it to the proteasome.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Deletion of ADRM1 by siRNA does not lead to global accumulation of ubiquitinated cellular proteins or changes in proteasome expression, suggesting that ADRM1 must have a specialized role in proteasome function (8). Shorty after the above report, three independent groups confirmed that ADRM1 is a novel 19S proteasome cap-associated protein, but they further revealed a unique role for ADRM1 in protein degradation (7,9,10). These groups found that ADRM1 interacts with the carboxyl-terminal tail of ubiquitin C-terminal hydrolase UCH37 and recruits it to the proteasome.…”
mentioning
confidence: 90%
“…One such protein is adhesion regulating molecule (ADRM1), which is recently identified as a novel proteasome-associated protein, which recruits the deubiquitinating enzyme UCH37 to the 26S proteasome (7)(8)(9)(10). Before this discovery, ADRM1 had been described as a heavily glycosylated membrane protein, which regulates cell adhesion (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…hRpn13, a component of the 19S regulatory subparticle of the 26S proteasome, is a major ubiquitin receptor [7], facilitating the docking of ubiquitinated proteins to the proteasome complex which ultimately leads to the degradation of the tagged protein. Interestingly, hRpn13 can also accelerate the deubiquitination process by recruiting the deubiquitinating enzyme UCH37 to the proteasome [22]. UCH37 is recently associated with the 19S regulatory particle that possesses robust deubiquitinating activity [14,26].…”
Section: Discussionmentioning
confidence: 99%
“…The 19S portion is responsible for stimulating 20S to degrade proteins [9,10]. hRpn13 is a component of the 19S particle, serves as a receptor for both ubiquitin and the deubiquitinating enzyme UCH37, and can also enhance the activity of UCH37 [16,22]. Therefore, it can be inferred that hRpn13 has bi-directional roles in modulating UPP activity.…”
Section: Introductionmentioning
confidence: 99%